Production of educational materials on COVID-19 and Hansen’s disease for the Guajajara and Canela indigenous peoples in the Legal Amazon of Maranhão, Brazil - Nepomuceno Borges, Síria Emerenciana (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
A Communicação, as a approach to preventive ações Em saúde indigenous na Amazônia legal maranhense - Brazil, feared as an objective skim -19, respectively. Or I study, on the side, criticism about the reason that I buy a few type of promotion to Saúde; And on an outro side, Demonstra uma exempliflifliflifição prat of elaboração of educational subjects mediated pela noção de equity em saúde collective. Ao analisar or Bank of Collection of Educational Matters on Hanseniase E Covid-19 da foundo swaldo Cruz (fiocruz), is found to the absence of voltmed material for indigenous povos. and you consider cases of cases for both sickness. Essa reality, which reflects Uma Falcha na Saúde Indigena, can be very serious when it is about Hanseniase, for the invisible to the indigenous people. A Situção Exposta Serviu, Portanto, from Argumentação for a produce of voltmed educational matters for or pov guajajara, not municipio of bar do corda e for or povo canela, not municipio of Fernando Falcão, two quais, using-be of uma instrumentalized methodological of Interdisciplinary Base-Indigenous History, Anthropology, Sick, Physiotherapy-E of Basic Formulações for Produce of Educational Matters Em Saúde Indigena-Bilíngue, Audiovisual and Easy Access Dois (02) Informative guides on a Hanseniase.